PENGARUH LITERASI EKONOMI DAN LITERASI DIGITAL TERHADAP MINAT BERWIRAUSAHA MAHASISWA - Jerni Hasmiah; Thamrin Tahir; Muhammad Hasan; Rahmatullah; Ihsan Said (Indonesian Journal of Economics, Entrepreneurship, and Innovation, 2021)
The purpose of this study was to determine the effect of economic literacy and digital literacy on entrepreneurial interest in students of the Economic Education Study Program, Faculty of Economics, Makassar State University. This study uses a quantitative approach with correlation research. Data collection techniques were carried out by observation and distributing questionnaires (questionnaires). The population in this study was 329 students of the 2017-2019 Economics Education Study Program, with a sample of 77 students. Data analysis technique using multiple linear regression. with the results of the study showing that partially the economic literacy variable has a positive and significant effect on the interest in entrepreneurship, and the digital literacy variable has a positive and significant effect on the entrepreneurial interest of the students of the Economic Education Study Program, Faculty of Economics, Makassar State University. And simultaneously the variables of economic literacy and digital literacy have a positive effect on the entrepreneurial interest of   students of the Economic Education Study Program, Faculty of Economics, Makassar State University.